A mythological folk story transformation to star focused on "Leylâ and Majnun" - Şenocak, Ebru (My University, 2010)
In the first period of history, men lived in nature and tried to arrange their daily activities according to sky and natural objects. Thus, depending on the creation of the Heavens God Religion, many beliefs have aroused on issues such as birth, death and etc. This study focuses on the last episode of the variants of "Leyla and Majnun" story where "the heroes are rising to the sky as stars". It aims to analyze the place of "Leyla and Majnun" story among the mythological folk stories by looking into the reasons for the beliefs based on stars and transforming into stars.
Mitolojik konulu bir halk hikâyesi "leylâ ile mecnûn hikâyesi" merkezinde yildiza dönüşüm
Keywords: Beliefs; Folk story; Leyla and majnun; Mythology; Stars